2019
DOI: 10.1007/s12105-019-01011-7
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Clinical Characteristics of 5294 Jaw Cysts: A Retrospective Study of 38 Years

Abstract: The aim of the present study is to report the demographic and clinical characteristics of all jaw cysts diagnosed in a single Oral Pathology Department. 5294 cases of jaw cysts diagnosed during a 38-year period were retrospectively collected and classified according to the latest classification of Head and Neck Tumors of the World Health Organization. The patients' gender and age, as well as the main clinical features of the cysts were retrieved from biopsy report forms. Jaw cysts were more common in male pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
46
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 29 publications
13
46
1
3
Order By: Relevance
“…Most of the studies show a male predominance while one study from Brazil showed results similar to ours. [ 1 4 5 7 10 17 18 ] OC's were seen to occur in a wide age range. 35.8% of cases were in the 21 to 40 age group, 29.8% in 41 to 60 age group 23.8% in 1 to 20 age group and 10.4% in people above 61 years with a mean age of presentation of 45.5% years.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies show a male predominance while one study from Brazil showed results similar to ours. [ 1 4 5 7 10 17 18 ] OC's were seen to occur in a wide age range. 35.8% of cases were in the 21 to 40 age group, 29.8% in 41 to 60 age group 23.8% in 1 to 20 age group and 10.4% in people above 61 years with a mean age of presentation of 45.5% years.…”
Section: Discussionmentioning
confidence: 99%
“…Autologous platelet-rich fibrin application lessens the severity of immediate postoperative sequelae, decreases preoperative pocket depth, and hastens bone formation in mandibular third molar extraction sockets (18). Among 5294 cases of jaw cysts diagnosed during a 38-year period, radicular cysts are most common followed by dentigerous, residual, and odontogenic keratocysts (19). During the period from January 2001 to December 2016 in Southern Taiwan, 232 patients, 133 females and 99 males at a mean age of 40.5 years (range, 13-78 with radicular cysts are diagnosed (20).…”
Section: Discussionmentioning
confidence: 99%
“…1 About half of the cases of cysts of the jaws comprise of inflammatory cysts, particularly, radicular cysts. 2 These form as a result of endotoxins released from an infected pulp canal followed by stimulation of epithelial rests in the periapical periodontal region of a tooth. 3 Performing root canal treatment or extraction of the involved tooth is deemed as an appropriate treatment for such cases.…”
Section: Introductionmentioning
confidence: 99%